Phenotypic and Genotypic Characterization of Candida parapsilosis complex isolates from a Lebanese Hospital - El Hady, Reine Clement (2023)
The opportunistic fungal pathogen C. parapsilosis is one of the major causative agents of candidosis in immunocompromised individuals. The azole fluconazole is the first line of defense in hospital treatment. Azoles function by inhibiting ERG11, an enzyme involved in the synthesis of ergosterol, the main sterol found in fungi. Resistance to azoles is on the increase worldwide including in Lebanon. The purpose of this study is to characterize nine hospital isolates labelled as C. parapsilosis: four resistant and five sensitive to fluconazole. Phenotypic characterization will be achieved through a battery of tests that target pathogenicity attributes such as virulence in a mouse model of disseminated candidosis, adhesion potential, biofilm formation, ergosterol and chitin content. Genotypic analysis will be done through whole genome sequencing to identify documented and novel SNPs and mutations in key virulence and resistance genes. Phylogenetic comparison of isolates will also be performed to determine strain relatedness and clonality. Our results showed that resistant isolates had no increased ergosterol content, or chitin deposition, no significant difference in virulence, but exhibited an increase in biofilm content compared with sensitive isolates. Genomic data and phylogenetic analysis revealed misidentification in three of our nine isolates. Two of the misidentified isolates, C. orthopsilosis and C. metapsilosis belong to the C. parapsilosis complex, while the third misidentified isolate was C. albicans. Moreover, several mutations in key drug resistance and virulence genes were identified (ERG11, ERG3, ERG6, CDR1, FAS2 and CFEM). These mutations might explain the phenotypes observed in our study. Phylogenetic analysis also revealed a high degree of relatedness and clonality within our C. parapsilosis isolates. In conclusion, our study suggests several mechanisms of antifungal drug resistance in C. parapsilosis Lebanese hospital isolates.